2009
DOI: 10.2134/agronj2008.0107x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Residue from Cereal Crops and Cultivars in Dryland Ecosystems

Abstract: Cropping systems in the dryland farming region of eastern Washington State are dominated by winter and spring wheat (Triticum aestivum L.) and spring barley (Hordeum vulgare L.). Excessive levels of residue may be an obstacle in the adoption of conservation farming systems. Decomposition of cereal crop residues is associated with fi ber and nutrient content, and growers have observed diff erences in decomposition among cultivars; however, little information exists on their residue characteristics. Cultivars of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
6
23
0
Order By: Relevance
“…35 Recently, interest in these biochemical plant fractions in the context of assessing crop suitability for bioproducts and biofuels has been building 36 and soil scientists are utilizing biochemical fractions to predict the decomposition of crop residues and the potential impact on soilx. 37 Using these fractions, we found that field pea was generally more readily degradable because of its lower % ADF and % ADL than canola, indicating that field pea would be higher in hemicellulose which is more easily degraded. 37 However, conclusions about degradability that are based on biochemical fractions cannot be assessed without considering the relative quantity of residues that each plant produces.…”
Section: Estimation Of Below-ground C Contributionmentioning
confidence: 95%
See 1 more Smart Citation
“…35 Recently, interest in these biochemical plant fractions in the context of assessing crop suitability for bioproducts and biofuels has been building 36 and soil scientists are utilizing biochemical fractions to predict the decomposition of crop residues and the potential impact on soilx. 37 Using these fractions, we found that field pea was generally more readily degradable because of its lower % ADF and % ADL than canola, indicating that field pea would be higher in hemicellulose which is more easily degraded. 37 However, conclusions about degradability that are based on biochemical fractions cannot be assessed without considering the relative quantity of residues that each plant produces.…”
Section: Estimation Of Below-ground C Contributionmentioning
confidence: 95%
“…37 Using these fractions, we found that field pea was generally more readily degradable because of its lower % ADF and % ADL than canola, indicating that field pea would be higher in hemicellulose which is more easily degraded. 37 However, conclusions about degradability that are based on biochemical fractions cannot be assessed without considering the relative quantity of residues that each plant produces. The balance between crop residue quantity and quality will ultimately dictate changes in soil processes and soil properties.…”
Section: Estimation Of Below-ground C Contributionmentioning
confidence: 95%
“…Decomposition of plant residues is largely mediated by microorganisms such as bacteria and fungi in the soil (3); the resultant nutritional carbon substrates can either support the growth of crops or be partially stored in the form of soil humus. Given the importance of decomposition in soil carbon sequestration, there has been continued interest in elucidating the dynamic changes of microbial communities during the course of residue decomposition (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Neutral detergent fiber (NDF) comprises the insoluble components of cell walls (cellulose, hemicellulose, and lignin). Acid detergent fiber (ADF) is a measure of cellulose and lignin [19].…”
Section: Initial Fiber Analysismentioning
confidence: 99%